The Impact Of Deforestation As An Idea In The Creation Of Painting - Nataprawira, Muhammad Rafli Ramdhani; Mustika, I Ketut; Setem, I Wayan (Program Studi Seni Murni ISI Bali, 2024)
This thesis contains a description of the creation of a work of painting with the theme